Faktor Imitasi Dalam Proses Pengambilan Keputusan Manajerial Oleh Wanita Tani Pada Usahatani Hortikultura Di Lahan Gambut - Anita Suharyani, Shenny Oktoriana, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2018)
The purpose of this research is to describe the factor of imitation behavior of women farmers on the decission making process for their farm management. This research was conducted with descriptive method to describe the relation between social environment and the farming decissions making for women farmers who cultivated horticulture on the peatland area at Limbung Village, Kubu Raya District. The result of the research showed that on the imitation behavior factor related to the decission making process by women farmers based on the social environment. Eventhough not all the decission was based on the behavior of other farmers, but the women farmers still considered other farmers decission. Therefore social enviroment became the important factor on the forming of women farmers behavior in running theiru farming, that reflected on the decissions they made.Keywords: imitation factor, farm management, women farmers, peatland farming